Protective effect of carvedilol versus vitamin E against MSG-induced ataxia model in rats through NRF2 modulation, Antioxidant and Antiapoptotic Effects - Ramadan, Eman; khriza, Mohamed; Hassanin, Amal; El-Salkh, Iman; A. E. Farrag, Eman (Journal of Neonatal Surgery, 2025)
Background: Carvedilol (CAR) is an adrenoreceptor antagonist used in cardiovascular disease management, such as congestive heart failure and hypertension. In addition to α and β receptor blockade, carvedilol shows additional antioxidant and anti-apoptotic effects. It has been included in research studies for many neurological conditions, but its utility in cerebellar ataxia has not been explored yet. This study sought to investigate the protective impact of carvedilol on cerebellar ataxia in rats using Monosodium glutamate (MSG). we aimed to evaluate its antiapoptotic and antioxidant properties, and to further compare its effect with vitamin E (Vit E). Materials and methods: For induction of ataxia, MSG (6g/kg/d) was injected intraperitoneally for 10 days. Twenty-four Sprague Dawley male rats, weight (180–200 g), age (8–10 weeks) were split randomly into four groups: control group, MSG group (6g/kg/day, Ip for 10 days), MSG + Vit E (250 mg/kg/day), orally for ten days, MSG+CAR (2 mg/kg/day), orally for 10 days. At the end of drug administration, behavioral assessment by rotarod was evaluated, and cerebellar tissue samples were collected from the sacrificed animals for histopathological, biochemical, and immunohistochemical studies. Results: The behavioral tests proved that treatment of rats with vitamin E has improved locomotor behavior in comparison to the MSG group. The rats showed increased latency and a decrease in the number of falls from the rotarod. In addition, biochemical analysis showed improvement in the vitamin E-treated rats, which was confirmed by increased GSH levels, reduction in the total ROS, and increase in NRF2 gene expression. The histopathological assessment with H&E showed a regain of almost normal histopathological features of the cerebellar neurons with a mild loss of Purkinje cells. Immune histochemical staining of cerebellar samples showed reduced positive staining of caspase-3 in most Purkinje cells. Carvedilol caused a significant improvement in the treated rats regarding all these parameters, which was less evident than the Vit E results. Conclusion: Both Vit E and carvedilol exhibited a protective effect in ataxia induced by MSG via upregulation of the NRF2 expression, exerting antioxidant effects and inhibiting apoptotic pathways.